A low jitter 50 Gb/s PAM4 optical receiver in 130 nm SiGe BiCMOS. (June 2023) - Lu, Shaorong; Xie, Sheng; Mao, Luhong; Song, Ruiliang; Zhang, Naibo
Abstract: This paper analyzed the causes of phase jitter in four-level pulse amplitude modulation (PAM4) optical receiver (ORX), and a modified architecture was proposed. An optimized shunt-feedback transimpedance amplifier was employed to suppress the random jitter caused by the noise of analog front-end, a three-lane limiting amplifier with inter-stage feedback was introduced to extend the bandwidth, and retimers aligning the edges of thermometer codes with an external clock were also incorporated. The ORX fabricated in 130 nm SiGe BiCMOS technology occupies an area of 1.125 mm 2 while dissipating 630 mW. The preliminary measured results demonstrated that the phase jitter of the most significant bit (MSB) was less than 0.08 UI for 25 Gb/s NRZ data. Post-layout simulation results indicate that our ORX can correctly decode 50 Gb/s PAM4 signal under a supply voltage of 3.3 V, and the peak-to-peak jitters for the MSB and the least significant bit (LSB) are only 1.5 ps and 2.9 ps, respectively.